Antecedents of fathers' perception of child behavior at child age 12 months. Issue 4 (9th June 2020) - Skjothaug, Thomas; Smith, Lars; Wentzel‐Larsen, Tore; Stänicke, Erik; Moe, Vibeke
ABSTRACT: This study investigates whether fathers' adverse childhood experiences (ACE) and attachment style reported during pregnancy predict fathers' perception of child behavior assessed 12 months postpartum, expressed by the Parenting Stress Index (PSI), Child Domain. Prospective fathers ( N  = 835) were recruited to "The Little in Norway (LiN) study" (Moe & Smith) at nine well‐baby clinics in Norway, with data collection composed of five time points during pregnancy and two time points postpartum (6 and 12 months). The main analyses included linear regression, path‐analysis modeling, and intraclass correlation based on mixed effects modeling. First, linear regression analyses showed that neither fathers' ACE nor attachment style significantly predicted perceived child behavior postpartum directly. Furthermore, path analyses showed that ACE and less secure attachment style (especially avoidant attachment) measured early in pregnancy strongly predicted negatively perceived child behavior, mediated by fathers' mental health symptoms during pregnancy and partner disharmony postpartum. Second, intraclass correlation analyses showed that fathers' perceived child behavior showed substantial stability between 6 and 12 months postpartum. Family interventions beginning in pregnancy may be most beneficial given that fathers' early experiences and perceptions of attachment in pregnancy were associated with later partner disharmony and stress. RESUMEN: Este estudio investiga si las experiencias adversas de los papás en su niñez y el estilo de afectividad reportado durante el embarazo predicen las percepciones de los papás sobre el comportamiento del niño según evaluación a los 12 meses después del parto, expresada por el Índice de Estrés de Crianza (PSI), Ámbito del Niño. Los papás con la posibilidad de participar (N = 835) fueron reclutados para el "estudio El Pequeño en Noruega (LiN)" (Moe y Smith, 2010) en nueve clínicas de revisión pediátrica en Noruega, con un proceso de recoger información compuesto de cinco momentos temporales durante el embarazo y dos momentos después del parto (6 y 12 meses). Los análisis principales incluyeron regresión lineal, diseños de análisis de trayectoria y correlación intraclase basados en diseños de efectos mixtos. Primero, los análisis de regresión lineal mostraron que ni las experiencias adversas de los papás en su niñez ni el estilo de afectividad predijeron significativamente la percepción del comportamiento del niño posterior al parto directamente. Es más, los análisis de trayectoria mostraron que las experiencias adversas en la niñez y un menos seguro estilo de afectividad (especialmente la afectividad esquiva) tal como fueron medidos a principios del embarazo predijeron fuertemente la percepción negativa del comportamiento del niño, todo lo cual fue mediado por los síntomas de salud mental de los papás durante el embarazo y la desarmonía de la pareja después del parto. Segundo, los análisis de correlación intraclase mostraron que la percepción que tenían los papás acerca del comportamiento del niño mostraba una estabilidad sustancial entre los 6 y 12 meses después del parto. Las intervenciones familiares que comienzan durante el embarazo pudieran ser más beneficiosas dado que las tempranas experiencias de los papás y sus percepciones de la afectividad durante el embarazo se asociaron con la posterior desarmonía y estrés de la pareja. RÉSUMÉ: Cette étude s'est interrogée si les expériences adverses de l'enfance des pères et le style d'attachement rapporté durant la grossesse prédisait la perception des pères du comportement de l'enfant évalué 12 mois après la naissance, exprimé par l'Index de Stress de Parentage (en anglais PSI), le Domaine de l'Enfant. Des pères potentiels (N = 835) ont été recruté pour l'étude norvégienne "The Little in Norway (LiN) study" (Moe & Smith, 2010) dans neuf cliniques de bien‐être du bébé en Norvège, avec un recueil de données comprenant cinq points de recueil durant la grossesse et deux après la grossesse (6 et 12 mois). Les analyses principales ont inclus une régression linéaire, une modélisation de l'analyse des trajectoires et une corrélation intraclasse basée sur une modélisation des effets mixtes. Tout d'abord, les analyses de régression linéaires ont montré que ni les expériences adverses vécues par les pères durant leur enfance ni le style d'attachement ne prédisait directement de façon importante le comportement de l'enfant perçu après la naissance. De plus les analyses de parcours ont montré que les expériences adverses vécues pendant l'enfance et le style d'attachement moins sécure (particulièrement l'attachement évitant) mesurés tôt dans la grossesse prédisaient fortement le comportement de l'enfant perçu négativement, médié par les symptômes de santé mentale des pères durant la grossesse et la discorde entre partenaires après la naissance. Deuxièmement les analyses de corrélation intraclasse ont montré que le comportement de l'enfant perçu des pères faisait preuve de stabilité substantielle entre 6 et 12 mois après la naissance. Des interventions sur la famille commençant durant la grossesse peuvent être plus bénéfiques au vu des expériences vécues des pères et les perceptions de l'attachement durant la grossesse étaient liées à la discorde ultérieure entre les partenaires et au stress. ZUSAMMENFASSUNG: Die Auswirkung väterlicher Vorerfahrungen auf die Wahrnehmung des Verhaltens 12 Monate alter Kinder In dieser Studie wurde untersucht, ob während der Schwangerschaft erhobene, aversive Kindheitserfahrungen und Bindungsstile des Vaters die väterliche Wahrnehmung des kindlichen Verhaltens vorhersagen können, die 12 Monate nach der Geburt durch den Parenting Stress Index (PSI) (Child Domain) gemessen wurden. N = 835 werdende Väter wurden in neun Well‐Baby‐Kliniken in Norwegen für die Studie „The Little in Norway (LiN)" (Moe & Smith, 2010) angeworben. Die Datenerhebung umfasste fünf Zeitpunkte während der Schwangerschaft und zwei Zeitpunkte nach der Geburt (6 und 12 Monate). Die Hauptanalysen bestanden aus linearer Regression, Pfadanalysemodellierung und Intraclass‐Korrelationen, basierend auf Mixed‐Effects‐Modellierung. Die linearen Regressionsanalysen zeigten, dass weder die aversiven Kindheitserfahrungen der Väter noch der Bindungsstil die Wahrnehmung des kindlichen Verhaltens unmittelbar nach der Geburt signifikant vorhersagten. Darüber hinaus zeigten Pfadanalysen, dass die zu Schwangerschaftsbeginn erhobenen, aversiven Kindheitserfahrungen und weniger sicheren Bindungsstile des Vaters (insbesondere vermeidende Bindung) negativ wahrgenommenes kindliches Verhalten vorhersagen konnten, mediiert durch psychische Symptome des Vaters während der Schwangerschaft und die Disharmonie in der Partnerschaft nach der Geburt. Die Intraclass‐Korrelationsanalysen zeigten, dass die väterliche Wahrnehmung des kindlichen Verhaltens zwischen 6 und 12 Monaten nach der Geburt eine erhebliche Stabilität aufwies. Bereits in der Schwangerschaft beginnende Familieninterventionen könnten einen positiven Effekt haben, da frühe Erfahrungen und die Bindungswahrnehmung des Vaters in der Schwangerschaft mit späterer Disharmonie und Stress in Verbindung gebracht werden konnten. 抄録: ヶ月児の行動に関する父親の認識に影響を及ぼす早期の原因 本研究では、妊娠中に報告された父親の逆境的な子ども時代の体験とアタッチメントのスタイルが、産後12か月時に実施された育児ストレスインデックス(PSI)の子どもの側面に表れた子どもの行動に関する父親の認識を予測できるかどうかについて調査した。父親になろうとしている人たち (N = 835) が、ノルウェーの9か所の育児相談において妊娠中5回と出産後2回(6ヶ月と 12ヶ月)にデータを収集した「リトル・イン・ノルウェー(LiN)研究」(Moe & Smith, 2010)の対象とされた。 おもな分析は、線形回帰分析、経路分析モデルと混合効果モデルを基にした級内相関を行った。第一に、線形回帰分析では、父親の逆境的な子ども時代の体験も、アタッチメントのスタイルも直接には出産後の子どもの行動に関する認識を優位に予測するものではないことが示された。さらに、経路分析では、逆境的な子ども時代の体験と妊娠初期測定された不安定なアタッチメントのスタイル(特に回避型アタッチメント) は、妊娠中の父親のメンタルヘルスの症状と出産後のパートナーとの不調和に介在され、子どもの行動を否定的に認識することを非常に強く予測することが示された。第二に、級内相関分析では、子どもの行動に関する父親の認識は、産後6ヶ月と12か月の間では、実質的な安定を示していた。妊娠中に始まる家族への介入は、父親の乳幼児期の体験と妊娠中のアタッチメントの認識が後のパートナーとの不調和とストレスに関係しているということにかなり有益であると思われる。 摘要: 本研究旨在探讨怀孕期上报的父亲的童年期不良经历和依恋方式是否能预测产后12个月父亲对儿童行为的感知力, 并以"父母压力指数量表 (PSI)"中的儿童分量表来表达。挪威的九家健康婴儿诊所招募了835名准父亲去参加"挪威儿童 (LiN) 研究" (Moe&Smith, 2010), 并收集了怀孕期间的五个时间点和产后 (6个月和12个月) 两个时间点的数据。本文主要采用了线性回归、路径分析模型以及基于混合效应模型的组内相关来分析这些数据。首先, 线性回归分析显示, 父亲的童年期不良经历和依恋方式对产后的儿童行为感知力均无直接预测作用。此外, 路径分析显示, 怀孕初期父亲的童年期不良经历和较不安全的依恋方式 (尤其是回避型依恋) 显著预测了其迟钝的儿童行为感知力, 这是由怀孕期父亲的心理健康状态和产后伴侣不和谐引起的。其次, 组内相关分析显示, 在产后6到12个月, 父亲的儿童行为感知力表现出显著的稳定性。鉴于怀孕期间父亲的早期经历和对依恋的感知力都与产后伴侣的不和谐及压力有关, 因此从怀孕开始就进行家庭干预可能是最为有益的。 ملخص: سوابق تصور الآباء للسلوك الطفولي في عمر 12 شهرا ملخص تبحث هذه الدراسة ما إذا كانت تجارب الطفولة السلبية للآباء وأسلوب التعلق المبلغ عنه أثناء الحمل تتنبأ بتصور الآباء لسلوك الطفل عند تقييمه بعد 12 شهر من الولادة ، وفقا لمؤشر الإجهاد الأبوي (PSI) ، مجال الطفل. تم تعيين الآباء المحتملين (N = 835) للمشاركة في الدراسة التي كان عنوانها "الصغير في النرويج LiN" التي أجراها (مو و سميث 2010(في تسع عيادات أطفال في النرويج ، مع جمع البيانات من خمس نقاط زمنية أثناء الحمل ونقطتين زمنيتين بعد الولادة (6 و 12 شهرًا). وشملت التحليلات الرئيسية الانحدار الخطي، ونمذجة تحليل المسارات، والارتباط داخل الفئات على أساس نمذجة الآثار المختلطة. أولاً، أظهرت تحليلات الانحدار الخطي أن تجارب الطفولة السلبية للآباء أو أسلوب التعلق لم يتنبأ بشكل كبير بسلوك الطفل المتصور بعد الولادة مباشرة. وعلاوة على ذلك، أظهرت تحليلات المسار أن تجارب الطفولة السلبية وأسلوب التعلق الأقل أمانا (وخاصة التعلق المتجنب الذي تم قياسه في وقت مبكر من الحمل تنبأ بشدة بالتصور السلبي لسلوك الطفل ، وتدخلت في ذلك متغيرات وسيطة أخرى مثل أعراض صحة الآباء النفسية أثناء الحمل وعدم التوافق بين الزوجين بعد الولادة. ثانياً، أظهرت تحليلات الارتباط أن تصور الآباء لسلوك الطفل أظهر استقراراً كبيراً بين 6 إلى 12 شهراً بعد الولادة. قد تكون التدخلات الأسرية التي تبدأ في الحمل مفيدة للغاية نظرًا لأن تجارب الآباء المبكرة وتصوراتهم للتعلق أثناء الحمل ارتبطت في وقت لاحق بتنافر الزوجين والإجهاد العصبي.